Effect of surface roughness on helicopter main rotor blade - W. N., W. Rohizan; Mohd.Rafie, Azmin Shakrine; Harmin, Mohammad Yazdi; Ciang, Chia Chen (Institute of Physics Publishing, 2016)
This paper describes the effect of surface roughness when applied on helicopter main rotor blade. The aim is to prove that surface roughness can be used as a simple and inexpensive method to achieve better flight performance such as enhanced thrust and/or reduced power requirement. The research was done experimentally, using scaled model of Eurocopter AS350 Ecureuil. Smooth profile of the main rotor blade was modified by applying surface roughness on the upper and lower camber in transition and turbulent boundary layer region, starting from 25% of chord length and extending up to the trailing edge (TE). This study was conducted with the conditions of a vertical flight (particularly in hover condition) since this is a high powerconsuming flight regime for helicopter. The experiment resulted in lower power requirement but at the expense of reduced thrust at the middle collective pitch level. At upper range of the collective pitch level, surface roughness was seen to delay the stall angle as well as increase the lift in the stall region. Meanwhile, at lower pitch level, there was an increase in thrust-to-power ratio.